ANALYZING COMPLAINTS BY INDONESIAN EFL SPEAKERS - Anna Marietta da Silva (Soegijapranata Catholic University, 2014)
The English language competence of an EFL learner can be reflectedin his pragmatic competence. Yet, for language learners and teachers a mastery of the pragmatic competence may unconsciously be neglected. In other words, it may not be taught in line with the grammatical competence since the initial period of learning. The article centers on two problems: (1) the similarities and differences of speech act of complaints among Indonesian EFL learners, Indonesian EFL teachers and American native speakers, and (2) the evidence of any pragmatic transfer in the complaint performance. DCT was used to gather the data, which was then analyzed using Rinnert, Nogami and Iwai?s aspects of complaining (2006). It was found that there were both differences and similarities of complaints performed by both the native and non-native speakers of English when power and social status were involved. Some evidence on pragmatic transfer was also tangible; mainly it was due to cultural differences